2017
DOI: 10.1155/2017/7526592
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Disorders and Environmental Toxicants: Epigenetics as an Underlying Mechanism

Abstract: The increasing prevalence of neurodevelopmental disorders, especially autism spectrum disorders (ASD) and attention deficit hyperactivity disorder (ADHD), calls for more research into the identification of etiologic and risk factors. The Developmental Origin of Health and Disease (DOHaD) hypothesizes that the environment during fetal and childhood development affects the risk for many chronic diseases in later stages of life, including neurodevelopmental disorders. Epigenetics, a term describing mechanisms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 246 publications
(217 reference statements)
0
89
0
4
Order By: Relevance
“…POPs were largely used in the industry, and, despite the ban on their use by the Stockholm Convention on Persistent Organic Pollutants in 2001, they can still be released into the environment mainly owing to the industrial emission or incineration of municipal and industrial waste (Esposito et al, ; Hung, Katsoyiannis, & Guardans, ; Trivedi & Majumdar, ). The World Health Organization (WHO) raised awareness about POP impact on environment and human health, thus encouraging several studies, which demonstrated the association of the exposure to these compounds with cancer development, reproductive problems, neurobehavioral disorders, abnormalities in fetal development, immune alteration, and disruption of hormones (Darras, ; Gregoraszczuk & Ptak, ; Hardell, Bavel, Lindstrom, Eriksson, & Carlberg, ; Lim et al, ; Tran & Miyake, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POPs were largely used in the industry, and, despite the ban on their use by the Stockholm Convention on Persistent Organic Pollutants in 2001, they can still be released into the environment mainly owing to the industrial emission or incineration of municipal and industrial waste (Esposito et al, ; Hung, Katsoyiannis, & Guardans, ; Trivedi & Majumdar, ). The World Health Organization (WHO) raised awareness about POP impact on environment and human health, thus encouraging several studies, which demonstrated the association of the exposure to these compounds with cancer development, reproductive problems, neurobehavioral disorders, abnormalities in fetal development, immune alteration, and disruption of hormones (Darras, ; Gregoraszczuk & Ptak, ; Hardell, Bavel, Lindstrom, Eriksson, & Carlberg, ; Lim et al, ; Tran & Miyake, ).…”
Section: Introductionmentioning
confidence: 99%
“…So, overall, increasing evidence has demonstrated that metals can act as carcinogens through different mechanisms. encouraging several studies, which demonstrated the association of the exposure to these compounds with cancer development, reproductive problems, neurobehavioral disorders, abnormalities in fetal development, immune alteration, and disruption of hormones (Darras, 2008;Gregoraszczuk & Ptak, 2013;Hardell, Bavel, Lindstrom, Eriksson, & Carlberg, 2006;Lim et al, 2017;Tran & Miyake, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of epigenetic changes that could lead to problems in early fetal brain development has been proposed . Environmental toxins or toxicants, such as those present in pollutants, cigarette smoke, heavy metal, drugs, and plastics, during fetal and childhood development or infection in a mouse model system have been shown to lead to abnormal DNA modifications .…”
Section: Epigenetics Of Autismmentioning
confidence: 99%
“…53 has been proposed. 54 Environmental toxins or toxicants, such as those present in pollutants, cigarette smoke, heavy metal, drugs, [55][56][57] and plastics, during fetal and childhood development or infection in a mouse model system 58 have been shown to lead to abnormal DNA modifications. 22,59,60 The study of epigenetics is more complicated than that of genetics because epigenetics of any tissue could change over time and varies with different tissues collected for the study.…”
Section: Possible Genetic Etiologymentioning
confidence: 99%
“…A previous study showed that the etiology of ASD may involve, at least in a subset of children, complex interactions between genetic factors and certain environmental toxicants that may act synergistically or in parallel during critical periods of neurodevelopment, in a manner that increases the likelihood of developing ASD (Rossignol et al, 2014). Another study found the epigenetic effects of environmental factors in humans that may affect normal neurodevelopment (Tran and Miyake, 2017). Environmental chemical exposure may contribute to increased autism prevalence (Sealey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%